Properties of CdS:Ni films prepared by chemical bath deposition method - Eitssayeam S. (2014)
Structural and morphological properties of Cds:Ni films prepared by chemical bath deposition (CBD) method were investigated. The asdeposited CdS films were found to be in cubic form which transform to hexagonal after annealing at temperature above 300 °C. It was found that the incorporation of ni concentration causes some damage regarding the crystallinity of CdS films. Results show that roughness and thickness increase with increasing Ni concentration.